2021
DOI: 10.1111/ejh.13595
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of thrombocytopenia in adult patients receiving chemotherapy for solid tumors or hematologic malignancies

Abstract: Objectives To estimate the risk of thrombocytopenia in various cancers and chemotherapy regimens. Methods Structured patient‐level data from the Flatiron Health Electronic Health Record database were used to identify adult patients who received chemotherapy for a solid tumor or hematologic malignancy from 2012 to 2017. Three‐month cumulative incidence of thrombocytopenia was assessed based on platelet counts, overall and by grade of thrombocytopenia. Co‐occurrence of anemia, neutropenia, and leukopenia was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…In a more recent analysis of 15,521 patients with solid tumors, 56 12.8% (95% CI: 12.3–13.4%) had CIT: grade 2 in 6.4%; grade 3 in 4.2% and grade 4 in 1.9%. CIT was more common in patients with solid tumors who received gemcitabine- and platinum-based regimens (14.8% and 13.5%, respectively) than in patients treated with anthracyclineor taxane-based regimens (9.3% and 6.5%, respectively).…”
Section: The Incidence Of Thrombocytopenia and The Use Of Platelet Tr...mentioning
confidence: 98%
“…In a more recent analysis of 15,521 patients with solid tumors, 56 12.8% (95% CI: 12.3–13.4%) had CIT: grade 2 in 6.4%; grade 3 in 4.2% and grade 4 in 1.9%. CIT was more common in patients with solid tumors who received gemcitabine- and platinum-based regimens (14.8% and 13.5%, respectively) than in patients treated with anthracyclineor taxane-based regimens (9.3% and 6.5%, respectively).…”
Section: The Incidence Of Thrombocytopenia and The Use Of Platelet Tr...mentioning
confidence: 98%
“… 5 A retrospective cohort study of 2537 patients with hematologic malignancies reported a 28% incidence of thrombocytopenia to <100 000/µL, with 16% of patients experiencing platelet counts <50 000/µL. 6 Certain chemotherapeutics used in the treatment of solid tumors such as gemcitabine and platinum-based agents are frequently associated with thrombocytopenia (30%-50% incidence), with platelet counts <50 000/µL occurring in 5% to 10% of patients. 7,8 The appropriate management of acute VTE and thrombocytopenia is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“… 2 CIT affects ~10% to 38% of solid tumor cancer patients and ~40% to 68% of patients with hematologic malignancies. 3 CIT can result from treatment with cyclophosphamide or other alkylating agents. 2 These agents can negatively affect pluripotent stem cells and megakaryocyte progenitors, the precursors from which platelets proliferate, in bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Thrombocytopenia resulting from chemotherapy varies by treatment regimen; however, there is an 82% incidence of CIT in patients who receive carboplatin monotherapy. 3 Similar to carboplatin, temozolomide (TMZ) is an alkylating agent; thus, we can expect similar thrombocytopenic side effects. Especially in combination with radiotherapy, temozolomide has the potential to cause thrombocytopenia in newly diagnosed high-grade glioma patients.…”
Section: Introductionmentioning
confidence: 99%